PENERAPAN MODEL PEMBELAJARAN BERMAIN PERAN (ROLE PLAYING) DALAM MATA PELAJARAN IPS TOKOH-TOKOH PAHLAWAN UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR SISWA SD NEGERI SENTUL JAYA 2 - Ahmad Sutiawan; Sudadio Sudadio; Lukman Nulhakim (Universitas Sultan Ageng Tirtayasa, 2022)
Study thisIaim for knowing the process of applying the learning model play role (Role Playing g) for increase results study and motivation State Elementary School students Sentul Jaya 2. With Theory know the characters _ hero method study conducted use study action class (CAR) with use three cycle , on every cycle his consist from planning , implementation , observation , and reflection . As for for results study his in the process of applying the learning model play role (Role Playing) for increase results study and motivation study State Elementary School students Sentul Jaya 2. meeting I on the first cycle the average value is 64.75 , the second meeting is 73.8 the average value of meeting I and II 71.7 whatever on cycle II meeting I the average value is 76 and meeting II 79.3 the average value of meeting I and II 77.65. As for cycle III the average value of the first cycle of the first meeting is 81 and meeting II 85, As for the average value is 84.86 . Based on test test on every cycle it turns out there is enhancement on every the cycle so that learning play role (Role Playing) fulfill criteria for used as a learning model on eye lesson social sciences (IPS).